Pathogenesis of Acanthamoeba Keratitis - Panjwani, Noorjahan (2010)
Acanthamoeba keratitis (AK) is a serious infection of the cornea. At present, diagnosis of the disease is not straightforward and treatment is very demanding. While contact lens wear is the leading risk factor for AK, Acanthamoeba parasites are increasingly recognized as an important cause of keratitis in non-contact lens wearers. The first critical step in the pathogenesis of infection is the adhesion of the microbe to the surface of the host tissues. Acanthamoebae express a major virulence protein, the mannose-binding protein (MBP), which mediates the adhesion of amoebae to the surface of the cornea. The MBP is a transmembrane protein with characteristics of a typical cell surface receptor. Subsequent to the MBP-mediated adhesion to host cells, the amoebae produce a contact-dependent metalloproteinase and several contact-independent serine proteinases. These proteinases work in concert to produce a potent cytopathic effect (CPE) involving killing of the host cells, degradation of epithelial basement membrane and underlying stromal matrix, and penetration into the deeper layers of the cornea. In the hamster animal model, oral immunization with the recombinant MBP protects against AK, and this protection is associated with an increased level of anti-MBP IgA in tears of protected animals. Normal human tear fluid contains IgA antibodies against Acanthamoeba MBP that is likely to provide protection by inhibiting the adhesion of parasites to host cells. Indeed, in in vitro CPE assays, even a low concentration of tears (10 [MU]μL of undiluted tears per milliliter of media) almost completely inhibits Acanthamoeba-induced CPE. In addition to adherence-inhibiting, IgA-mediated protection, human tears also contain IgA-independent factors that provide protection against Acanthamoeba-induced CPE by inhibiting the activity of cytotoxic proteinases. Characterization of the CPE-inhibitory factors of human tears should lead to a better understanding of the mechanism by which the tissues of the host resist the infection and also help decode circumstances that predispose to Acanthamoeba infections.